Expeditionary anthropology teamwork, travel and the 'science of man' - Thomas, Martin 1964-; Harris, Amanda 1976- (Methodology and history in anthropology, 2018)
The origins of anthropology lie in expeditionary journeys. But since the rise of immersive fieldwork, usually by a sole investigator, the older tradition of team-based social research has been largely eclipsed. Expeditionary Anthropology argues that expeditions have much to tell us about anthropologists and the people they studied. The book charts the diversity of anthropological expeditions and analyses the often passionate arguments they provoked. Drawing on recent developments in gender studies, indigenous studies and the history of science, the book argues that even today, the 'science of man' is deeply inscribed by its connections with expeditionary travel.